Effect of Seed Rate and Spacing on Yield and Economics of Isabgol (Plantago ovata Forsk.) - Shivran, A C (Annals of Arid Zone, 2016)
A field experiment was conducted to work out optimum seed rate and spacing for isabgol variety ‘GI-2’ isabgol at SKN College of Agriculture, Jobner, during rabi seasons of 2002-03 and 2003-04. The treatments were 4, 6 and 8 kg ha-1 seed rate and sowing at 15, 20, 25 and 30 cm row spacings and broadcasting. Results indicated that 8 kg ha-1 seed rate significantly reduced spikes/plant and seeds/spike, whereas, significantly increased seed, straw and biological yields (1321, 3672 and 4993 kg ha-1, respectively) of isabgol over 4 and 6 kg ha-1 seed rates. Positive effect of seed rate was not marked on test weight, harvest index and husk recovery. Significantly maximum net returns (Rs. 31,175 ha-1) and benefit:cost ratio (3.69) were also recorded with 8 kg seed ha-1. The sowing of crop at 25 cm row spacing, being at par with 20 and 30 cm, recorded significantly highest spikes/plant, seeds/spike, test weight, seed (1315 kg ha- 1), straw (3598 kg ha-1), biological yields (4913 kg ha-1), net returns (Rs. 31,104 ha-1) and B:C ratio (3.73) over 15 cm row spacing and sowing by broadcasting. The spacing could not bring significant change in harvest index and husk recovery. Key words: Isabgol, seed rate, spacing, yield, net returns, benefit:cost ratio.